Determination of the occlusal plane in completely edentulous patient by computerized cephalometric method (A comparative study). Part I - Nadira A Hatim; Inas A Jawad (Al-Rafidain Dental Journal, 2006)
Aim: to determine the validity of the ala–tragus technique in orienting the occlusal plane in complete denture construction for edentulous patients by evaluation of the edentulous patient response. Materials and methods: Twenty edentulous patients were selected according to specific criteria. Sixty sets of complete dentures (three sets for each edentulous patient) with three different occlusal planes parallel to the imaginary line between the inferior border of the ala of the nose, and superior, middle and inferior borders of the tragus were constructed. The grade of participants' response in this research was studied to report the degree of their participation with the occlusal plane of the complete denture they used through answering of Denture Patient Satisfaction Questionnaire (DPSQ) after one month of using each of the three randomly selected complete dentures. Mean and percentage of all the scores (four scores totally satisfied and unsatisfied, fairly satisfied and unsatisfied) were calculated to give an idea about the participants' response. Results: showed greatest participants’ satisfaction (75–90%) were obtained in the complete denture with middle and inferior occlusal planes. Patients satisfaction with denture 2 range between 80–90% regarding speech and chewing ability. Denture 3 (inferior occlusal plane) showed the greatest fairly satisfaction in 60% of patients originated from mandibular denture. Conclusion: most patients were satisfied with the dentures having occlusal plane be oriented parallel to the middle and inferior ala–tragus lines.